MENELUSURI ABJEKSI SUBJEK DALAM NOVEL AYAH KARYA ANDREA HIRATA: KAJIAN SEMIOTIKA REVOLUSIONER JULIA KRISTEVA - Arifin, Moch. Zainul (Kantor Bahasa Banten, 2018)
This paper attempts to explain the figure of a mother who is not from the body of a mother or woman, but motherhood can also be owned by a man. While Dad does not only refer to men but also to women. Therefore, it cannot be viewed in an anatomical-biological point of view, but as a union between Mother-Father, the Imaginary Father. From both of them form unconscious semiotic human beings so that indirectly humans will try to find more comfort than what has been obtained from the mother's function. So that the subject continues to process something else in order to interpret his personal experience. In novel Ayah written by Andrea Hirata shows the motherly nature in a man and the figure of a father in a woman so that their child has semiotic unconsciousness. By looking at this, from Kristeva's theory of revolutionary semiotics proposed in dissecting the novel. And it was found that Zorro as a child had saved his chora experience in shirts, poetry and stories. He also did not understand why he could act in this way, but it made him comfortable and socially providing additional comfort from his semiotic unconsciousness. After being discussed at length, it is assumed that Zorro experienced a comforting abjection because maternal function is not considered dirty, disgusted, and dangerous. But it was helped by the Imaginary Father figure who finally knew the language and social Zorro. Because of the pleasant abjection, Zorro cannot forget the love, warmth, and affection of the mother figure for him forever.